Jelita Cosmetic Store’s Marketing Strategy to Attract Consumers on Jalan Tamansiswa, Yogyakarta - Alfa Khoirun Nisa (LifeSciFi, 2026)
This study aims to analyze the marketing strategies implemented by Toko Jelita Cosmetic to attract and retain customers amidst the competitive cosmetics industry in Yogyakarta. This research used a qualitative descriptive method with a Systematic Literature Review (SLR) approach combined with limited interviews. Data analysis was conducted thematically by integrating literature findings and empirical data. The results indicate that Jelita Cosmetic’s marketing strategy is dominated by the implementation of the 4Ps marketing mix: product, price, place, and promotion. Its main advantages lie in competitive pricing and attractive promotions, such as discounts and bundling, which are effective in increasing consumer purchasing interest, particularly among students. Furthermore, a comprehensive product variety, strategic location, and friendly service contribute to increased customer satisfaction and loyalty. However, limited store space and parking hinder customer convenience. This study demonstrates that value-based marketing strategies and customer experience are crucial for the success of local cosmetics retailers.